The shorter Routledge encyclopedia of philosophy - Craig, Edward, 1942- (Routledge, 2005)
The Shorter REP presents the very best of the acclaimed ten volume Routledge Encyclopedia of Philosophy in a single volume. It makes a selection of the most important entries available for the first time and covers all you need to know about philosophy, from Aristotle to Wittgenstein and animals and ethics to scientific method. Comprising over 900 entries and covering the major philosophers and philosophical topics, The Shorter REP includes the following special features: Unrivalled coverage of major philosophers, themes, movements and periods making the volume indispensable for any student or general reader Fully cross-referenced Revised versions of many of the most important entries, including fresh suggestions for further reading Over twenty brand new entries on important new topics such as Cloning and Sustainability entries by many leading philosophers such as Bernard Williams, Martha Nussbaum, Richard Rorty, Onora O'Neill, T.M. Scanlon and Anthony Appiah Striking new text design to help locate key entries quickly and easily An outstanding guide to all things philosophical, The Shorter Routledge Encyclopedia of Philosophy provides an unrivalled introduction to the subject for students and general readers alike.